Microarchitectural study of the augmented bone following ridge preservation with a porcine xenograft and a collagen membrane: preliminary report of a prospective clinical, histological, and micro-computed tomography analysis. Issue 2 (February 2017) - Kivovics, M.; Szabó, B.T.; Németh, O.; Tari, N.; Dőri, F.; Nagy, P.; Dobó-Nagy, C.; Szabó, G.
Abstract: Socket preservation using a combination of porcine xenograft and collagen membrane maintains the vertical and horizontal dimensions of the ridge. The aim of this study was to evaluate the microarchitecture of the grafted area by histological analysis and micro-computed tomography. Patients in the test group (group 1; nine patients) underwent socket preservation, while the sockets in the control group (group 2; eight patients) were allowed to heal without preservation. After a 6-month healing period, bone core biopsy samples were obtained and implants were placed in the augmented sites in the test group (12 biopsy samples) and the non-augmented sockets of the control group (12 biopsy samples). Analysis of the biopsy samples obtained from group 1 revealed that particles of the graft were surrounded by newly formed bone in eight cases and by granulation tissue in four cases. Micromorphometric data showed statistically significant differences in several parameters between the microarchitecture of the native bone and the newly formed bone within the augmented sites, which suggests that the xenograft particles interfere with the bony healing of the alveoli.